Experimental investigations of a vibro-impact absorber attached to a continuous structure. (15th November 2022) - Chabrier, R.; Chevallier, G.; Foltête, E.; Sadoulet-Reboul, E.
Abstract: Vibro-impact (VI) phenomenon can be used in vibration absorbers to reduce low frequency vibrations on a fast time scale. VI absorbers are effective on a wide range of frequency, they are also known to be robust and insensitive to temperature changes, and they do not rely on visco-elastic materials. This solution offers very interesting and promising possibilities for vibration suppression in harsh environments where classical solutions can be pushed to their limits. If previous works have extensively studied VI based solutions numerically, mostly applied to single degree of freedom systems, experimental works dealing with continuous and multi-modal structures have received less attention. The work proposed in this paper focuses on the vibration reduction of a beam using a VI absorber with adjustable clearance. A parametric study on the clearance of the absorber has been performed. The response of the beam under harmonic excitation demonstrates the existence of an optimal clearance that leads to the lowest level of vibration of the beam. A relation between the gap value, the excitation amplitude and the response is found and can be translated into an attractive scalability property. The well-known regimes with two impacts per cycle and the Strongly Modulated Regime (SMR) have been clearly identified on the beam response, their relation with the optimal design of the absorber is highlighted, and their mechanism is explained. The present results open up new perspectives for vibro-impact absorbers, especially concerning their technological development and optimal design. Highlights: A modular vibro-impact absorber with tunable gap is designed to mitigate the vibrations of a beam. Efficiency for two modes is demonstrated experimentally for harmonic and random excitations. A classification of the regimes in clusters using the number of impacts as a feature is provided. Optimal operating point and occurrence of specific regimes are related. Motion reconstruction is performed thanks to full-field measurements and digital image correlation.